A short review of material combination in Bilayer Electrolyte of IT-SOFC - Mat Z.A.; Kar Y.B.; Yong T.C.; Hassan S.H.A. (Science Publishing Corporation Inc, 2023)
The technology of solid oxide fuel cell (SOFC) is attractive as it is considered as one of promising clean energy due to its efficiency and clean production of electricity. However, high operating temperature of SOFC are main issue in range of applications such as in transportation and portable equipment. One of many goals of SOFC is to lower the operating temperature. Bilayer electrolyte has become one of the solution in order to reduce the high operating temperature. This review article provides the preliminary information of bilayer electrolyte in order to achieve high performance at intermediate temperature. 2018 Authors.